2015
DOI: 10.1088/0957-4484/26/8/085204
|View full text |Cite
|
Sign up to set email alerts
|

Axial p–n-junctions in nanowires

Abstract: The charge distribution and potential profile of p-n-junctions in thin semiconductor nanowires (NWs) were analyzed. The characteristics of screening in one-dimensional systems result in a specific profile with large electric field at the boundary between the n- and p- regions, and long tails with a logarithmic drop in the potential and charge density. As a result of these tails, the junction properties depend sensitively on the geometry of external contacts and its capacity has an anomalously large value and f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2017
2017
2018
2018

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 21 publications
(42 reference statements)
0
1
0
Order By: Relevance
“…In addition to the evaluation of dopant and electrostatic profiles, the photovoltaic (PV) performance of NW axial p–i–n junctions has been evaluated theoretically as well as in devices composed of single NWs and large-area NW arrays. In devices, it has been shown that a reduction in surface recombination results in significantly improved performance, boosting both photocurrent and photovoltage. ,,,,, Though recombination may place an upper bound on device performance, it is not the sole determinant.…”
mentioning
confidence: 99%
“…In addition to the evaluation of dopant and electrostatic profiles, the photovoltaic (PV) performance of NW axial p–i–n junctions has been evaluated theoretically as well as in devices composed of single NWs and large-area NW arrays. In devices, it has been shown that a reduction in surface recombination results in significantly improved performance, boosting both photocurrent and photovoltage. ,,,,, Though recombination may place an upper bound on device performance, it is not the sole determinant.…”
mentioning
confidence: 99%